Toward a Filipino Christology - Asis, Michael Demetrius H. (Budhi: a Journal of Ideas and Culture, 2018)
Current research on the Historical Jesus challenges Filipino Christology to do a "Christology from Below" --emphasizing the struggles and humanity of Jesus in first century Palestine as an appropriate starting point for a meaningful and relevant Filipino Christology today. Are our current Jesus images mere projections of our deep desire to fashion him in our own image? Or are they grounded on real, historical facets of his life? Any re-appropriation of the memory of the Jesus of history must, for the most part, become honest appropriations of the spirit of Jesus' historical life and message, which focused on realizing the kingdom of God, particularly on behalf of the worlds' poor and marginalized.